Jenis Kata Dalam Tuturan Masyarakat Diglosik Gang Baru Semarang - Sutarsih, Sutarsih (Kementerian Sekretariat Negara Republik Indonesia, 2017)
Gang Baru is one of the multiethnic areas in Semarang city. Chinese community in this area is able to speak more than one language. They often switch from one language into another in their daily spoken language. The switch shows that Chinese people in Gang Baru is a diglossic community. Data source for this research is the utterances of the Chinese community in Gang Baru. Data is collected by listening and conversational methods. Data is analyzed by functional descriptive and contextual method. Result of analysis in the utterances is five word classes: pronoun, numeral, adjective, adverb, and verb. The words are not only from Indonesian language, but also from Javanese, Dutch, English, and Chinese. Keywords: word class, utterance, diglossic, Gang Baru.